Hepatic Ischemia-Reperfusion Impairs Blood-Brain Barrier Partly Due to Release of Arginase From Injured Liver - Zhu, Liang; Zhou, Han; Xu, Feng; Yang, Hanyu; Li, Ping; Sheng, Yun; Liu, Peihua; Kong, Weimin; Liu, Xiaonan; Yang, Lu; Liu, Li; Liu, Xiaodong (Frontiers in Pharmacology, 2021)
Aim: Hepatic ischemia-reperfusion (HIR) induces remote organs injury, including the brain. The homeostasis of the brain is maintained by the blood-brain barrier (BBB); thus, we aimed to investigate whether HIR impaired BBB and attempted to elucidate its underlying mechanism. Methods: Cell viability of human cerebral microvascular endothelial cells (hCMEC/D3) was measured following 24 h incubation with a serum of HIR rat undergoing 1 h ischemia and 4 h reperfusion, liver homogenate, or lysate of primary hepatocytes of the rat. The liver homogenate was precipitated using (NH4)2SO4 followed by separation on three columns and electrophoresis to identify the toxic molecule. Cell activity, apoptosis, proliferation, cell cycle, and expressions of proteins related to cell cycle were measured in hCMEC/D3 cells incubated with identified toxic molecules. HIR rats undergoing 1 h ischemia and 24 h reperfusion were developed to determine the release of an identified toxic molecule. BBB function was indexed as permeability to fluorescein and brain water. Endothelial cell proliferation and expressions of proteins related to the cell cycle in cerebral microvessels were measured by immunofluorescence and western blot. Results: Toxic molecule to BBB in the liver was identified to be arginase. Arginase inhibitor nor-NOHA efficiently attenuated hCMEC/D3 damage caused by liver homogenate and serum of HIR rats. Both arginase and serum of HIR rats significantly lowered arginine (Arg) in the culture medium. Arg addition efficiently attenuated the impairment of hCMEC/D3 caused by arginase or Arg deficiency, demonstrating that arginase impaired hCMEC/D3 via depriving Arg. Both arginase and Arg deficiency damaged hCMEC/D3 cells by inhibiting cell proliferation, retarding the cell cycle to G1 phase, and downregulating expressions of cyclin A, cyclin D, CDK2, and CDK4. HIR notably increased plasma arginase activity and lowered Arg level, increased the BBB permeability accompanied with enhanced brain water, and decreased the proliferative cells (marked by Ki67) in cerebral microvessels (marked by CD31) and protein expressions of cyclin A, cyclin D, CDK2 and CDK4 in isolated brain microvessels. Oral supplement of Arg remarkably attenuated these HIR-induced alterations. Conclusion: HIR leads to substantial release of arginase from the injured liver and then deprives systemic Arg. The Arg deficiency further impairs BBB via inhibiting the proliferation of brain microvascular endothelial cells by cell cycle arrest.